2020
DOI: 10.1177/0363546520920546
|View full text |Cite
|
Sign up to set email alerts
|

Introducing the Lateral Femoral Condyle Index as a Risk Factor for Anterior Cruciate Ligament Injury: Letter to the Editor

Abstract: The authors declared that they have no conflicts of interest in the authorship and publication of this contribution. AOSSM checks author disclosures against the Open Payments Database (OPD). AOSSM has not conducted an independent investigation on the OPD and disclaims any liability or responsibility relating thereto.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…In knees without this notch, however, there can be uncertainty and randomness in determining the most inferior points. 15 We observed 2 types of ambiguous geometries of the distal lateral femoral condyle that made it difficult to draw accurate circles, both of which did not include this notch: (1) a horizontal connection between the anterior and posterior aspects of the condyle (Figure 2); and (2) a sloped line connecting the anterior and posterior aspects of the condyle (Figure 3). When the notch is absent, multiple sizes of the extension circle can fit the criteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In knees without this notch, however, there can be uncertainty and randomness in determining the most inferior points. 15 We observed 2 types of ambiguous geometries of the distal lateral femoral condyle that made it difficult to draw accurate circles, both of which did not include this notch: (1) a horizontal connection between the anterior and posterior aspects of the condyle (Figure 2); and (2) a sloped line connecting the anterior and posterior aspects of the condyle (Figure 3). When the notch is absent, multiple sizes of the extension circle can fit the criteria.…”
Section: Discussionmentioning
confidence: 99%
“…First, the measurement of this index can entail uncertainty and randomness due to potential ambiguity in the protocol. 15 Second, the experimental group of patients with ACL injury was heterogeneous in terms of their injury mechanism (ie, data from contact and noncontact mechanisms were combined) 15 even though the literature shows that the majority of ACL injuries are caused by a noncontact mechanism, 1,6 when tibiofemoral geometry most likely has the greatest role. Third, the LFCI was measured in the injured knee of the patients with primary ACL injury, which assumes the trauma did not modify geometric characteristics of the knee.…”
mentioning
confidence: 99%
“…In other words, the flexion circle and extension circle were drawn before and after the lateral femoral condyle, respectively, and the ratio of the radius of the two circles was considered the lateral femoral condyle index [ 10 ]. However, Li et al indicated that the two circles had great uncertainty and randomness, possibly leading to large errors of this measurement method [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the exion circle and extension circle were drawn before and after the lateral femoral condyle, respectively, and the ratio of the radius of the two circles was considered the lateral femoral condyle index [10]. However, Li et al believed that the two circles had great uncertainty and randomness, so this measurement method may have large errors [20].…”
Section: Discussionmentioning
confidence: 99%